2017
DOI: 10.1002/anie.201701146
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane‐Intercalating Conjugated Oligoelectrolyte with High‐Efficiency Photodynamic Antimicrobial Activity

Abstract: A membrane-intercalating conjugated oligoelectrolyte (COE), PTTP, was designed and synthesized with the goal of providing red-shifted absorption spectra relative to previously synthesized COE analogs. Specifically, electron-rich and electron-poor subunits were introduced in the conjugated backbone to modulate the band gap. PTTP exhibits maxima of absorption at 507 nm and of emission at 725 nm. PTTP can also efficiently function to generate singlet oxygen in situ (Φ ≈20 %) and has appropriate topology and dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 44 publications
(17 reference statements)
3
148
0
Order By: Relevance
“…The zeta potential of E. coli was negative (−13.3 mV), which was increased to positive (15.6 mV) when 5 μ m of TBD‐anchor was added to the E. coli mixture (Supporting Information, Figure S14). This result suggests that TBD‐anchor could effectively bind to bacteria …”
Section: Methodsmentioning
confidence: 94%
“…The zeta potential of E. coli was negative (−13.3 mV), which was increased to positive (15.6 mV) when 5 μ m of TBD‐anchor was added to the E. coli mixture (Supporting Information, Figure S14). This result suggests that TBD‐anchor could effectively bind to bacteria …”
Section: Methodsmentioning
confidence: 94%
“…In addition, they established the protocol for quantifying 1 O 2 generation by using SOSG , and demonstrated that quantitative measurements of 1 O 2 can be achieved directly by determining the reaction rate in the condition of the order of reaction with respect to SOSG equals zero. These protocols have been widely adopted to visualize the formation of 1 O 2 in U937 cells and to determine the 1 O 2 quantum yield of the newly developed photosensitizers . The direct method proposed by them is based on the direct detection of near‐infrared NIR luminescence of 1 O 2 around 1270 nm using NIR photomultiplier tubes (R5509‐43/H10330‐45, Hamamatsu, Japan).…”
Section: Selected Research Achievementsmentioning
confidence: 99%
“…Taking advantage of the membrane accumulating ability of aromatic substituents, Bazan et al. prepared a membrane‐intercalating conjugated oligo electrolyte that showed high antibacterial ability upon irradiation . Current evidence indicates that PSs that exhibit high photobiological outcome are constituted by dyes that besides positive charge have a well‐balanced lipophilicity.…”
Section: Introductionmentioning
confidence: 99%